Pengaruh Aliran Kas Bebas Dan Keputusan Pendanaan Terhadap Nilai Pemegang Saham Dengan Set Kesempatan Investasi Sebagai Variabel Moderating - Munandar, Bambang Tri; Kusumawati, Rita (Universitas Muhammadiyah Yogyakarta, 2017)
The purpose of this study was to examine the effect of free cash flow and funding decisions on shareholder value with investment opportunity set as a moderating variable. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2010 until 2015. Data collected by purposive sampling method and the sampling results obtained are 93 companies.sampel. The analysis technique used moderated regression analysis (MRA) or interaction test.The test results show that free cash flow has no significant effect on shareholder value, while funding decisions have significant effect on shareholder value, investment opportunity set can moderate the effect of free cash flow to shareholder value, investment opportunity set can moderate influence of funding decision to value shareholders